A SPECTRUM OF Β-THALASSEMIA MUTATIONS IN SULAIMANI PROVINCE OF IRAQ: IDENTIFICATION OF NOVEL MUTATIONS - Ahmad, Narmeen Salih; Karim, Hersh Abdul Ham; Rasool, Luqman Khalid; Ali, Khanzad Ahmed; Mahmood, Mohammed Abdalla; Osman, Tara Jamel; Hamakhan, Chawan Wrya (Journal of Sulaimani Medical College, 2025)
Background β-thalassemia is a most common hereditary disease where the patients suffer from decreased or absence of beta-globin chain synthesis, which leads to hemolytic anaemia and other complications. Very little data about beta-globin mutations in the Kurdish population is available to date. Objective This study aimed to provide a more precise picture of the β-thalassemia mutations spectrum and to estimate their frequencies. Methods A cohort of 100 β-thalassemia patients was tested to detect mutations in the beta-globin gene’s regions (3 exons and two introns) using molecular techniques (polymerase chain reaction and Sanger sequencing). Results In this study, a total of 31 beta-thalassemia mutations were identifi ed. The results showed that IVSII-666 C>T and IVSII-16 G>C were predominant over other mutations, with 59% of thalassemic patients having these mutations. Other common mutations found, in order of decreasing frequency, were Cd2 T>C, IVSII-74 T>G, IVS1-110 G>A, IVSI-5 G>C, IVSII-1 G>A, IVSII-81 C>T. The remaining mutations were uncommon and accounted for a few cases. More importantly, fi ve novel beta-thalassemia mutations, namely, IVSII-13 G>A, IVSII-14 A>C, IVSII-17 delC, IVSII-68_69 dupG, and Cd2/3 +C, were discovered which have not been previously reported in other populations. Conclusion The results obtained in this study can be used as a guide before prenatal diagnosis and during premarital screening of β-thalassemia in the Kurdish population.
Keywords: βThalassemia; Mutation; Beta globin gene; Polymerase chain reaction; Sanger sequencing